Coordination-driven self-assembly of a molecular figure-eight knot and other topologically complex architectures - Li-Long Dang (Nature Portfolio, 2019)
Molecular knots and links continue to fascinate synthetic chemists. Here, the authors use stacking and hydrogen-bonding interactions between a set of similar building blocks to construct several complex molecular topologies, including a figure-eight knot and a trefoil knot.